Towards perfectly linearly polarized X-rays - Schulze, Kai S.; Grabiger, Benjamin; Loetzsch, Robert; Marx-Glowna, Berit; Schmitt, Annika T.; Garcia, Alejandro Laso; Hippler, Willi; Huang, Lingen; Karbstein, Felix; Konopkova, Zuzana; Schlenvoigt, Hans-Peter; Schwinkendorf, Jan-Patrick; et al. (Physical Review Research, 2022)
In recent years, high-precision X-ray polarimeters have become a key method for the investigation of fundamental physical questions from solid-state physics to quantum optics. Here, we report on the verification of a polarization purity of better than 8×10-11 at an X-ray free-electron laser, which implies a suppression of the incoming photons to the noise level in the crossed polarizer setting. This purity provides exceptional sensitivity to tiny polarization changes and offers intriguing perspectives for fundamental tests of quantum electrodynamics.
CRIS-Team Scopus Importer:2023-04-20